Study on physicochemical status, bacterial analysis and its correlation - Islam, MS; Rahman, MM; Mahabub, Z; Haque, Nurullah; Mahmood, MM; Alauddin, Md; Mamun, MA; Hosain, MM; Rony, MA; Rana, MR; Ahammed, Shakil; Uddin, Md Nasir; et al. (The Mattingley Publishing Co., Inc., 2020)
Swimming pool, as a recreational facility is now a part of current lifestyle that offers social and health benefits. More demand for hotels with swimming pool facility and are highly used during peak seasons. However swimming pool could become a pooling medium of various bacteria came from the bathers, air and soils thus risk of water-borne disease and impose hazard to human health. Therefore, a well disinfected swimming pool that meets the minimum standard requirement must be reached. This study aimed to assess the status of physicochemical parameters including free chlorine, pH, and temperature and to assess status of bacteria analysis of swimming pool water samples. 11 swimming pool water samples were taken from hotels in Klang valley, Malaysia. The physicochemical parameters were tested using colorimetric method using N,N-diethyl-1,4-phenylenediamine and bacteria analysis were obtained by standard plate count (SPC) method. Results are presented in mean and standard deviation. Correlation coefficient is obtained by Pearson’s correlation statistical test. Results showed mean of temperature 29.64±1.430C, pH 7.56±0.40, free chlorine 1.22±1.16 ppm and bacterial SPC 4,825.64±8,409.16cfu/ml. Correlation-coefficient between temperature and SPC r: 0.71. The findings showed current physicochemical status of hotel swimming pool water samples met the minimum standard requirement. However, the bacterial SPC is highly above acceptable range and positively correlated to temperature. This indicates bacterial count increase with temperature rise despite of acceptable chlorine level. The acceptable level of chlorine as disinfectant is insufficient to oxidize bacteria thus may put the swimming pool water at risk of spreading water borne diseases. This finding suggests increase dosage of chlorine is required to maintain swimming pool sanitation during hot season in order to provide a safe water recreational facility. However, larger sample size is required to confirm the findings website.